Lussazione dell’articolazione sternoclavicolare - D'Arrigo, C.; Rota, P.; De Sanctis, S. (Lo Scalpello - Journal, 2019)
DISLOCATION OF STERNOCLAVICULAR ARTICULATIONDislocation of the sternoclavicular joint is a rarely injury. Dislocations can be anterior or posterior. Anteriordislocation is a usually relatively benign injury, while posterior dislocations may be very serious. In addition to thestandard projections, there are also special views for joint evaluation. Computed tomography remains the goldstandard. In anterior dislocations, and degree I and II posterior instability, the treatment is conservative, while in caseof degree III dislocations, the treatment consists in closed reduction. Operative stabilisation must be considered ifclosed reduction is unsuccessful.